CITIZEN CENTERED MODELS USING MOBILE TECHNOLOGY APPLICATIONS FOR M-GOVERNMENT - Nugraheni, Dinar Mutiara Kusumo (MATEMATIKA, 2011)
This research paper will present an existing application and the opportunity m-government services base on mobile technology applications. First we examine the existing applications in mobile technology that can be used for m-government services around world. Secondly, we will look at the benefit and disadvantages those mobile technology applications for m-government services. In addition, it will provide an overview the development of ICT in Indonesia and recognizing the particular challenges that exist for e-government in Indonesia. Then, we will create an analysis as the citizen centered models for m-government base on smart phone mobile technology application.